An interdisciplinary learning approach to ecological business : using examples of best practice - Valentukevičienė, Marina (Array, 2020)
It is a widely held view among educationists that the most effective way to facilitate a holistic learning approach is to present visual, ready-to-use, practical examples. Thus, our study follows the general scope of the course “Socially responsible ecological business”, which is currently offered to master students at the Vilnius Gediminas Technical University (VGTU). We contend that teaching materials should be presented visually using case studies and examples. Indeed, simple guidance is one of the vital learning tools for students. Accordingly, and in line with the aims of the course, the observations and experience of differences in global culture and our inclusion of a wide range of ecological examples were central to the design of our international case study. In particular, students found the case study on ecological business both useful and applicable in the real world.